2014
DOI: 10.1136/annrheumdis-2013-204698
|View full text |Cite
|
Sign up to set email alerts
|

Signature of circulating microRNAs in osteoarthritis

Abstract: Background Osteoarthritis is the most common form of arthritis and a major socioeconomic burden. Our study is the first to explore the association between serum microRNA levels and the development of severe osteoarthritis of the knee and hip joint in the general population. Methods We followed 816 Caucasian individuals from 1995 to 2010 and assessed joint arthroplasty as a definitive outcome of severe osteoarthritis of the knee and hip. After a microarray screen, we validated 12 microRNAs by real-time PCR in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
124
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 35 publications
3
124
0
2
Order By: Relevance
“…Our recent ability to profile unique patterns of epigenetic changes offers novel strategies for distinguishing diverse chondrocyte phenotypes that relate to chondrogenic programming, articular cartilage homeostasis, and OA disease progression, and for identifying novel biomarkers of early OA, such as circulating long non-coding RNAs and miRNAs [154,155]. Correlating DNA methylation, chromatin marks, and miRNA signatures in human OA disease with those found in well-defined OA animal models could allow us to define the different regulatory requirements for stress-related phenotypes of OA chondrocytes [156].…”
Section: Prospects For the Futurementioning
confidence: 99%
“…Our recent ability to profile unique patterns of epigenetic changes offers novel strategies for distinguishing diverse chondrocyte phenotypes that relate to chondrogenic programming, articular cartilage homeostasis, and OA disease progression, and for identifying novel biomarkers of early OA, such as circulating long non-coding RNAs and miRNAs [154,155]. Correlating DNA methylation, chromatin marks, and miRNA signatures in human OA disease with those found in well-defined OA animal models could allow us to define the different regulatory requirements for stress-related phenotypes of OA chondrocytes [156].…”
Section: Prospects For the Futurementioning
confidence: 99%
“…MiRNAs frequently exhibit imperfect complementarity with their target strands, which allows one specific miRNA to inhibit the expression of multiple genes [7]. Recently, a number of studies have been published pertaining to the role of miRNAs in both inflammatory and neuropathic pain conditions [8][9][10], and a few studies have successfully applied circulating miRNAs as biomarkers in pain conditions such as osteoarthritis, complex regional pain syndrome (CRPS), fibromyalgia, and irritable bowel syndrome in humans [8,[11][12][13][14][15]. Additionally, a pioneering study highlighted the ability of interstitial miR-let-7b to induce pain through an extracellular mechanism involving the coupling between Toll-like receptor-7 and the nociceptive ion channel transient receptor potential cation channel subfamily A [16].…”
Section: Introductionmentioning
confidence: 99%
“…miR-146 is another miRNA that is highly expressed in low-grade OA cartilage and is induced by IL-1β stimulation; additionally, it mediates chondrocyte apoptosis (13,14). In serum, Beyer et al recently reported miRNA let-7e as a potential predictor for severe knee or hip OA (15).…”
Section: Introductionmentioning
confidence: 99%